Kajian Pemanfaatan Gas Metan Dari Tahun 2017 Hingga Tahun 2020 Dan Prediksi Hingga Tahun 2030 Penggunaan Sebagai Sumber Energi Pada Kawasan Mandiri Energi Kota Kendari – Indonesia - Yuspian Gunawan (Universitas Halu Oleo, 2021)
Abstract — This study aims to analyze the amount of methane gas, the amount of electricity, the amount of plastic waste, and the potential for pyrolysis oil produced from the amount of organic waste managed in the last 4 years (2017, 2018, 2019, and 2020). The method used in this research is the